IMPROVEMENT OF HEMOGLOBIN LEVELS IN PREGNANT WOMEN WITH ANEMIA THROUGH DRAGON FRUIT CONSUMPTION - Rahmiati -; Jasmawati -; Lukman Nulhakim (Departement Research and Community Engagement Bina Sehat PPNI Institute of Health Science, Indonesia, 2023)
Pregnant women are at risk of experiencing anemia, which can have health impacts such as bleeding and giving birth to low birth weight babies (LBW). The global prevalence of anemia is 43%, while in Indonesia it is 37.1%, and in the Rantau Pulung Community Health Center (Puskesmas) area, it is 39.3%. Efforts to address low hemoglobin levels often involve regular consumption of iron tablets during pregnancy. Non-pharmacological interventions include the consumption of dragon fruit, rich in vitamin C, vitamin B1, vitamin B2, vitamin B3, and protein, to increase hemoglobin levels. To determine the influence of dragon fruit on increasing hemoglobin levels in pregnant women with anemia in the working area of the Rantau Pulung Community Health Center. This study utilized a quasi-experimental design with a pre-test post-test non-equivalent control group. The study population included a total of 26 pregnant women with anemia. The sampling technique used was total sampling, resulting in 26 participants divided into an experimental group of 13 and a control group of 13. The measurement tool was observation of hemoglobin levels. Data analysis employed paired t-tests and independent t-tests. There was a difference in hemoglobin levels before and after the administration of iron tablets combined with dragon fruit by 1.1692 g%, and a difference in hemoglobin levels before and after the administration of iron tablets by 0.7077 g%. The administration of iron tablets combined with dragon fruit was effective in increasing hemoglobin levels in pregnant women in the working area of the Rantau Pulung Community Health Center in East Kutai Regency, with a p-value of 0.004. Consuming 500 g of dragon fruit daily can increase the hemoglobin levels of pregnant women due to its content of vitamin C, vitamin B1, vitamin B2, vitamin B3, and protein. The administration of dragon fruit effectively increases hemoglobin levels in pregnant women.